Funcionarios de la Oficina de Transportes. (UNED, 2024)
Aparecen de izquierda a derecha Carlos Luis Retana Romero, Manuel Antonio Porras Vargas, William Villalobos Chavarría, Jorge Rojas Aguero, En el mismo orden, sentados, Rodrigo Mora Soto, Minor Solano Corella, José Joaquín Solano Zeledón (Gastón)